Structural basis of regulated N-glycosylation at the secretory translocon - Melvin Yamsek; Mengxiao Ma; Roshan Jha; Yu Wan; Qianru Li; Frank Zhong; Katherine DeLong; Zhe Ji; Rajat Rohatgi; Robert J. Keenan (Nature, 2026)
Abstract Most human secretory pathway proteins are N-glycosylated by oligosaccharyltransferase (OST) complexes as they enter the endoplasmic reticulum (ER) 1–3 . Recent work revealed a substrate-assisted mechanism by which N-glycosylation of the chaperone glucose-regulated protein 94 (GRP94) is regulated to control cell surface receptor signalling 4 . Here we report the structure of a natively isolated GRP94 folding intermediate tethered to a specialized CCDC134-bound translocon. Together with functional analysis, the data reveal how a conserved N-terminal extension in GRP94 inhibits OST-A and how structural rearrangements within the translocon shield the tethered nascent chain from inappropriate OST-B glycosylation. These interactions depend on a hydrophobic CCDC134 groove, which recognizes a non-native conformation of nascent GRP94. Our results define a mechanism of regulated N-glycosylation and illustrate how the nascent chain remodels the translocon to facilitate its own biogenesis.